2012
DOI: 10.1073/pnas.1202214109
|View full text |Cite|
|
Sign up to set email alerts
|

The costimulatory immunogen LPS induces the B-Cell clones that infiltrate transplanted human kidneys

Abstract: The mechanism of chronic rejection of transplanted human kidneys is unknown. An understanding of this process is important because, chronic rejection ultimately leads to loss of the kidney allograft in most transplants. One feature of chronic rejection is the infiltration of ectopic B-cell clusters that are clonal into the transplanted kidney. We now show that the antibodies produced by these B-cells react strongly with the core carbohydrate region of LPS. Since LPS is a costimulatory immunogen that can react … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…Independent of immunosuppression, infections of the urinary tract or posttransplant alterations of the UMB may well lead to additional immune dysregulation and consequent immune‐mediated graft injury. In fact, two recent papers from our laboratory group demonstrate that antibodies produced by B cell clusters commonly found in the biopsies of IFTA subjects are not recognizing donor HLA antigens but rather are specific for Escherichia coli Lipopolysaccharide, a powerful immune activator through the canonical TLR4 receptor . Another of our studies identified the role of a new mycoplasma protein, obtained from a potential human urinary pathogen, as a powerful, polyclonal B cell activator .…”
Section: Introductionmentioning
confidence: 79%
“…Independent of immunosuppression, infections of the urinary tract or posttransplant alterations of the UMB may well lead to additional immune dysregulation and consequent immune‐mediated graft injury. In fact, two recent papers from our laboratory group demonstrate that antibodies produced by B cell clusters commonly found in the biopsies of IFTA subjects are not recognizing donor HLA antigens but rather are specific for Escherichia coli Lipopolysaccharide, a powerful immune activator through the canonical TLR4 receptor . Another of our studies identified the role of a new mycoplasma protein, obtained from a potential human urinary pathogen, as a powerful, polyclonal B cell activator .…”
Section: Introductionmentioning
confidence: 79%
“…B-cell receptor specificity for bacterial lipopolysaccharide (LPS) has been recently identified in B cells infiltrating and expanding within human renal allografts undergoing chronic rejection (232). Since LPS can react in these cells with both the BCR and TLR4, these observations led the authors to speculate on the possibility that infection and the attendant exposure to LPS play a role in the chronic rejection of human kidney transplants.…”
Section: Impact Of Infections On the Alloreactive B-cell Repertoire Amentioning
confidence: 99%
“…Clonal B-cell proliferation, as well as lymphomas and myelomas, can result from chronic infections with organisms such as Escherichia coli ( E. coli ) and Helicobacter pylori ( H. pylori ) (16). The main feature seems to be the approximation of two systems each capable of sustained replication where the replicating microbe induces proliferation and selection of members of the replicating B-cell repertoire.…”
mentioning
confidence: 99%